ADVANCED CONSTRUCTED WETLANDS FOR WASTEWATER TREATMENT IN HOT AND ARID CLIMATE - Mr. Aditya Ramesh Nannaware; Prof. P. A. Hangargekar; Prof. D. C. Poul; Prof. S. C. Wadne (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This study presents a novel Advanced Constructed Wetland (ACW) system for efficient wastewater treatment in hot climate regions. The ACW incorporates a unique arrangement of mixed media blocks, including soil, sawdust, zeolite, and biochar, to enhance pollutant removal. The system is designed to achieve high treatment efficiencies for organic matter, nutrients, and emerging contaminants, while minimizing the required footprint. Experimental results demonstrate the effectiveness of the ACW in treating domestic wastewater and septic tank effluent. The system effectively removes organic matter, nutrients, and pharmaceuticals and personal care products (PPCPs). The presence of ammonia-oxidizing archaea and bacteria in the media layers contributes to the conversion of ammonia to nitrogen gas. The ACW system offers a promising solution for sustainable wastewater management in arid and semi-arid regions. Its innovative design and high treatment efficiency make it a valuable addition to the available wastewater treatment technologies.